REPOSITIONING OUR THINKING: USING CULTURALLY RESPONSIVE PRACTICES TO INCREASE EQUITABLE ACCESS TO RIGOROUS INSTRUCTION. - Dupree, Leon R (East Carolina University, 2023)
A teacher's work is to enhance their knowledge and skills of effective teaching while making sure that every students needs are met through their teaching practices. The Participatory Action Research (PAR) study examined the extent to which teachers changed their practices by engaging in culturally responsive practices with a Co-Practitioner Researcher (CPR) team and transferring those practices to the classroom. I formed a Co-Practitioner Researcher (CPR) team of four teachers and an instructional coach and facilitated the co-creation of a learning environment in which we could engage in dialogue and co-generate culturally responsive pedagogical practices that address rigor in the classroom. Using the methodology of participatory action research and focusing on the community learning exchange axioms, the CPR team engaged in the three inquiry cycles. By purposefully working in collaborative structures to identify effective strategies and components of rigor, using community learning exchange pedagogies, and cultivating an appropriate learning environment, the CPR team co-created an observational tool that identified rigor in their teaching practices. These findings are based on evidence from a three-cycle inquiry process in which we constructed meaning from the data.: (1) Teachers require appropriate learning conditions that foster their development as adult learners.; (2) creating rigorous instruction for students is a developmental process for teachers, and (3) teachers transfer their learning to practice when they have opportunities for peer dialogue and input on observation processes. As a team, we engaged as a community of practice committed to engaging in collaborative activities, discussions about the classroom, and being active practitioners to transfer practice to the classroom. The important application is the methods we used for meeting and learning together about the critical work of focusing on rigor in middle school classrooms.
Keywords: Rigorous instruction; Culturally relevant pedagogy; Educational equalization; Middle school students; Active learning